Lipid Droplet and Peroxisome Biogenesis: Do They Go Hand-in-Hand? - Joshi, Amit S.; Cohen, Sarah (Frontiers in Cell and Developmental Biology, 2019)
All eukaryotic cells contain membrane bound structures called organelles. Each organelle has specific composition and function. Some of the organelles are generated de novo in a cell. The endoplasmic reticulum (ER) is a major contributor of proteins and membranes for most of the organelles. In this mini review, we discuss de novo biogenesis of two such organelles, peroxisomes and lipid droplets (LDs), that are formed in the ER membrane. LDs and peroxisomes are highly conserved ubiquitously present membrane-bound organelles. Both these organelles play vital roles in lipid metabolism and human health. Here, we discuss the current understanding of de novo biogenesis of LDs and peroxisomes, recent advances on how biogenesis of both the organelles might be linked, physical interaction between LDs and peroxisomes and other organelles, and their physiological importance.